The Determination of Electronic Goods Inventory at Rahmah Store Using the Fuzzy Tsukamoto Method - Jannah, Ghina Raodatul; Bittara, Andi Ghizzania Sirih; Udin, Alvin Mas; Nasrullah, Asmaul Husna; Adiba, Fhatiah (Media of Computer Science, 2024)
Toko Rahmah is faced with the challenge of determining the optimal inventory of electronic goods to avoid excess or shortage of inventory. The uncertainty of demand and large sales often leads to inefficient inventory management. This study aims to apply the Tsukamoto fuzzy method in determining the optimal inventory of electronic goods at Toko Rahmah. Using this method will increase the accuracy of managing inventory and reduce the risk of excess or shortage of inventory. Therefore, in this study, the Tsukamoto fuzzy method is used to model and overcome the uncertainty of electronic goods inventory. Sales and demand data serve as output to the fuzzy system. The steps taken include forming a fuzzy set, applying fuzzy rules, and performing defuzzification to get an output value that is used as an inventory quantity recommendation. The results of this study were tested using 2 ways, namely using the Netbeans application system and using excel. These two ways are done to see how accurate or suitable the results obtained are. The accuracy results show that the average accuracy is 0.41 from 22 existing data, which is where the system is able to provide fairly accurate recommendations in determining the inventory of goods at Toko Rahmah. This method reduces the risk of excess or shortage of inventory and increases efficiency in managing inventory.